The Significance of Heat Transport by Shallow Fluid Flow at an Active Plate Boundary: The Southern Alps, New Zealand. Issue 19 (5th October 2018) - Coussens, Jamie; Woodman, Nicholas; Upton, Phaedra; Menzies, Catriona D.; Janku‐Capova, Lucie; Sutherland, Rupert; Teagle, Damon A. H.
Abstract: Fluid flow can influence fault behavior. Here we quantify the role of groundwater heat advection in establishing the thermal structure of the Alpine Fault, a major tectonic boundary in southern New Zealand that accommodates most of the motion between the Australian and Pacific Plates. Convergence on the Alpine Fault has rapidly uplifted the Southern Alps, resulting in high geothermal gradients and a thin seismogenic zone. A new equilibrium temperature profile from the 818‐m‐deep Deep Fault Drilling Project 2B borehole has been interrogated using one‐dimensional analytical models of fluid and rock advection. Models indicate a total heat flux of 720‐mW m −2 results from groundwater flow with Darcy velocities approximating to 7.8 × 10 −10 m s −1 . Groundwaters advect significantly more heat than rock advection in the shallow orogen (<6‐km depth) and are the major control on the subsurface temperature field. Plain Language Summary: The behavior of geological faults is dependent on temperature, pressure, and the nature rocks at the fault plane, all of which may be influenced by groundwater. The Alpine Fault forms the boundary between the Pacific and Australian tectonic plates through South Island, New Zealand. In the past it has generated large earthquakes approximately every 300 years. The fault rapidly uplifts ( 10 mm/yr) Pacific plate rocks to form the Southern Alps. These rocks move to the surface too fast to cool by conduction and carry significant heat to the near surface. Here temperature measurements from the 818‐m‐deep Deep Fault Drilling Project 2B borehole, adjacent to the Alpine Fault, have been used to investigate how groundwater flow influences subsurface temperatures near the fault. Simple 1‐D models of the measured borehole temperature profile indicate that the heat flow near the Alpine Fault is over 10 times greater than typical continental crust. Groundwater flow, driven by ridge‐valley topography in the Pacific plate and further influenced by localized fracture zones and sequences of valley‐fill sediment, transports over 3 times more heat than the uplift of rocks alone. This groundwater regime is therefore key to understanding the thermal regime and earthquake generation on the fault. Key Points: Data from Deep Fault Drilling Project borehole 2B in the Southern Alps show a heat flux of 720 mW m −2, exceeding typical continental values Fluid flow with Darcy velocity approximating to 7.8 × 10 −10 m s −1 transports >3 times more heat than rock advection Groundwater flow, modified by highly fractured zones and sediment fills, is a key control on temperatures at depths <6 km in this orogen